Open innovation ecosystems in the software industry - Gençer, M.; Oba, B. (Palgrave Macmillan, 2014)
Computers have an increasing variety of uses in virtually every aspect of our personal life and work-related activities. Children from early ages play games on tablets, Grandma uses a small digital device to track her blood pressure, and parents work with smartphones and laptops during their commutes. A common characteristic of computers is that, for the most part, they rely on software to accommodate different uses. © Refik Culpan, 2014.